Security sector reform in Bosnia and Herzegovina. A case study of the Europeanization of the Western Balkans - Kudlenko Anastasiia (Comparative Southeast European Studies, 2017)
Security sector reform (SSR) has become an important part of the EU’s efforts to transform the Western Balkans from a conflict-ridden area into a stable and democratic part of Europe. This paper studies SSR in Bosnia and Herzegovina (BiH) as an illustration of the multifaceted and complex Europeanization policies employed by the EU in the region. It does not present a study of the European Security and Defence Policy (ESDP) missions, as there is already a wealth of material available on this subject, but offers instead a broader examination of changes in two sectors of BiH’s security system with the aim of improving understanding of the EU’s impact on the domestic environments of candidate states. Its main argument is that the EU used police and intelligence reforms in Bosnia, both of which were part and parcel of the SSR efforts in the country, as state-building tools. But because domestic competence in Bosnia was lacking and the EU was rather inexperienced in implementing SSR, the reforms have had a mixed record of success and reveal the limitations of the region’s Europeanization.